An overview of chemical constituents from Alpinia species in the last six decades. Issue 23 (2nd March 2017) - Ma, Xiao-Ni; Xie, Chun-Lan; Miao, Zi; Yang, Quan; Yang, Xian-Wen
Abstract : Alpinia species is one of the most important genera of the Zingiberaceae family. Up to 2015, 544 compounds with various bioactivities were isolated, the major components are diarylheptanoids (143) and sesquiterpenoids (132). Abstract : Alpinia species is one of the most important genera of the Zingiberaceae family. In Asia, they have been widely used as food and traditional medicines for centuries. This review focuses on their chemical constituents and their relevant biological activities with 252 references covering from 1955 to 2015. In total, 544 compounds were isolated from 35 Alpinia species. The major ones are terpenoids (207) and diarylheptanoids (143). The crude extracts and identified compounds exhibited a broad spectrum of bioactivities including antiemetic, antiulcer, antibacterial, anti-inflammatory, anti-amnesic, anticancer, etc.